Social Education Regarding Healthy Living and First Aid When a Heart Attack Occurs - Lestari, Dhina Lydia; Gusmira , Yuni Handayani; Ma’arif , Mashdarul; Amelia, Ade Yuli (Universitas Pahlawan Tuanku Tambusai, 2024)
Abstract Heart attacks can attack anyone, not only old people but also young people. Sudden death is most often caused by a heart attack. Sudden cardiac arrest is an unexpected cause of death without previous trauma, which occurs within a short time, usually less than 1 hour from the onset of symptoms. As many as 75% of the causes of sudden heart attacks. However, until now the local community has not known about preventing first aid when a heart attack occurs properly and correctly, and an unhealthy lifestyle greatly affects our heart health. Therefore, the aim of this community service is to see what factors are behind unhealthy lifestyles in society which can cause heart attacks to occur in today's society and provide education to the public regarding first aid methods for preventing heart attacks in the community. In obtaining the data used were observation and literature study. This service activity is an effort to educate healthy lifestyle behaviors to prevent heart attacks in Air Pacah Village, Koto Tangah District, Padang City, West Sumatra. This effort is motivated by a lack of knowledge about healthy lifestyles. As a form of the author's thinking, several efforts and breakthroughs are offered, namely: 1.) The public is given knowledge on how to adopt a healthy lifestyle as an effort to prevent heart attacks, 2.) The public is given education on how to provide first aid when a sudden heart attack occurs, 3.) Community prevention efforts are made by building groups that care about healthy lifestyle and prevention of heart attacks from village or sub-district level to district or city and provincial levels so that it is hoped and provides knowledge and prevents deaths due to heart attacks. Keywords : Healthy Lifestyle, Heart, Heart Attack